The Economy of Cities: Discussion - Fox, Karl A. (American Economic Review, 1970)
KARL A. Fox: Most of my comments will relate to the paper by Jane Jacobs. Mrs. Jacobs is to be commended for her concern about urban problems and also for attempting to think about these problems in a systematic way. However, she gives us no definition of a city nor does she seem to recognize that a definition is needed. Lacking insight into the economic structure of the basic unit of her system, she also fails to provide us with useful criteria for policy intervention. I cannot operate with Mrs. Jacobs' categories. We need a much better framework for conceptualizing urban economic structure than she has given us. key to this better framework lies in central place theory, a field actively pursued by quantitative geographers but strangely neglected by most economists. I will begin by presenting my view of the structure of the United States economy as a hierarchy of central places. Quantitative geographers recognize about eight levels of central places in the United States: hamlets, villages, towns, small cities (e.g., county seats), regional capitals, regional metropolitan centers, national metropolitan centers, and the national (economic) capital. Hamlets and villages are relics of the horse-andbuggy era. Towns (perhaps 1,000 to 5,000 people), small cities (perhaps 5,000 to 25,000 people), and regional capitals (usually with 25,000 to 250,000 people) form a three-level hierarchy which (together with the farm and nonfarm village, hamlet, and opencountry population) forms the basic ecological pattern of our nonmetropolitan areas in the automobile age. regional capital is the central city of a hometo-work commuting field of approximately an hour's radius. Since 1961, I have been calling such a commuting field a economic or FEA. Such an area is a relatively self-contained labor market in the short run. It is also relatively self-contained in terms of other characteristics and systems such as department store trade areas, radio and TV broadcasting areas, newspaper advertising areas, community colleges; area vocational-technical schools, and medical and legal services. A functional economic area may be regarded as a low-density city or rural-urban synthesis covering up to 5,000 square miles, equivalent to several midwestern counties. regional capital contains the central business district of the FEA as a whole, as well as the largest and most diversified array of employment opportunities. Virtually all residents of the FEA are aware of the central city and make some use of it. In the Midwest, the total populations of FEA's will usually range from 100,000 to 500,000, even though their regional capitals as such contain only 25,000 to 250,000 people. Ordinarily, few workers residing in one FEA commute to jobs located in other FEA's. Perhaps 60 percent of all jobs in an FEA are oriented to the needs of its own residents: retailing, public services, personal and professional services, and the like. remaining 40 percent or so of jobs in an FEA are in activities which are primarily export-oriented from the standpoint of that FEA. Two FEA's with the same population size and average income level will have almost identical arrays of resident-oriented jobs; the resident-oriented components of the two labor forces should be almost as interchangeable as the crews of two sister ships. National chains of department stores and national advertising of consumer goods both reflect and reinforce this basic similarity and interchangeability. two FEA's may differ substantially in their arrays of jobs which are primarily export-oriented. Agriculture, most mining and manufacturing, large federal installations, state capitols and state universities (among other activities) are primarily export-oriented from the standpoint of the FEA in which they are located. complete distributions of wage and salary incomes, occupational skills, educational attainments, and potential community leadership in two such FEA's result from their similar arrays of resident-oriented jobs and their more or less dissimilar arrays of export-oriented jobs. functional economic area is the basic building block of the national system of cities in the United States. resident-oriented activities and individual households in each FEA can be regarded as forming a sort of macro-household; the export-oriented activities form an intercity trading and input-output system which links the several hundred FEA's into a truly national economy. three-stage central place hierarchy of a nonmetropolitan FEA (town, small city, and regional capital) has its analog in the three-stage hierarchy of shopping centers found in the larger metropolitan areas: neighborhood shopping centers (serving from 15,000 to 30,000 people), district shopping centers (serving perhaps 60,000 to 120,000 people), and regional shopping plazas (serving as many as 500,000 people). A regional shopping plaza usually contains a major branch of a large downtown department store; few residents of the trade area of the regional shopping plaza make much use of the shopping facilities in the central business district of the metropolis as a whole. Therefore, as consumers, most residents of the major metropolitan areas are clustered into functional * papers by Jane Jacobs, Strategies for Helping Cities, Barbara R. Bergmanni, The Urban Economy and the 'Urban Crisis,' and Anthony Downs, Housing the Urban Poor: Economics of Various Strategies, were printed in the Sept., 1969, issue of A.E.R. but presented at this session.